Problematic internet use and their relationship with personality traits / I.D Safairis Amat Noor - Amat Noor, I.D Safairis (2016)
Internet has become an integral part of our daily life. Since the existence of Internet, it does not only help us to communicate with each other, but also has become one of the main source of obtaining information, connecting between electronic devices and applications, provides entertainment, increasing work productivity and many other necessary purposes. Despite the Internet being beneficial to our daily life it also comes with side effects. As our culture becomes increasingly dependent on such technologies, it is not surprising that some individuals demonstrate problematic Internet use. Ease of access to Internet provides an escape route to dysfunctional behaviors and maladaptive cognitions where compensation theory suggests that psychological and/or social problems in a person's life can lead to excessive Internet use; as these individual experience problems in their daily lives, they use the Internet as a way to compensate for their problems. This aspect of personality related characteristics, often examined by Five Factor Model (FFM) is commonly used and accepted as a comprehensive representation of personality traits. This study aimed to investigate the existence of problematic Internet use and the relationship with personality traits among working adults at the workplace. An ICT organization in Malaysia was selected as target respondent where Internet can be easily accessible through personal device and employer-provided assets. This research discussed on various studies conducted against problematic Internet use, and the relation with personality trait factors, using descriptive and statistical analysis method. Questionnaires was converted into webpage and conducted on 104 sample of respondents in an ICT organization. The results obtained using structural equation modelling indicated that there was a significant relationship between the constructs of three factors of problematic Internet use such as neglect, obsession and control disorder and four factors of personality traits such as agreeableness, conscientiousness, openness and emotional stability except extraversion factor. Implications of the current findings as well as limitations and future directions are discussed.